Amplifying dementia as a global public health problem: A cross-country comparison of the impact of COVID-19 pandemic. (October 2021) - Giebel, Clarissa; Lion, Katarzyna; Mackowiak, Maria; Chattat, Rabih; Suresh Kumar, PN; Cations, Monica; Gabbay, Mark; Moyle, Wendy; Ottoboni, Giovanni; Rymaszewska, Joanna; Senczyszyn, Adrianna; Szczesniak, Dorota; et al.
Abstract : Background: Emerging evidence describes impacts of the COVID-19 pandemic upon people living with dementia and their informal carers, however without evidence-based global comparisons to date. The aim of this international study was to explore and compare the impact of COVID-19 and associated public health restrictions on the lives of people living with dementia and informal carers and access to dementia care across five countries. Methods: People with dementia and informal carers from the UK, Australia, Italy, India, and Poland participated in remote semi-structured interviews. Participants were asked about their experiences of the pandemic and how restrictions have impacted on their lives and care. Transcripts were analysed by researchers in each country using thematic analysis, then combined across sites. Results: Fifteen people living with dementia and 111 informal carers participated across the five countries. Four themes emerged: (1) Limited access and support; (2) Technology and issues accessing remote support; (3) Emotional impact; and (4) Decline of cognitive and physical health reported by carers. Whilst variations were noted, the pandemic has indirectly affected people with dementia and carers across all five countries. The pandemic removed access to social support services and thus increased carer burden. Remote services were not always provided and were limited in benefit and usability for those with dementia. Carers frequently described noticeably deteriorating cognitive and physical health in people with dementia. Conclusions: The pandemic has amplified dementia as a global public health problem, and both people affected by the condition ad their carers need support to better access vital support services to live well. This is even more important with emerging new waves and new variants of the virus affecting different countries, in our globally connected world.